2022
DOI: 10.1088/1742-6596/2349/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO nanoparticles by co-precipitation technique and characterize the structural and optical properties of these nanoparticles

Abstract: The present work demonstrates synthesis and study of physical properties of chemically synthesized ZnO nanoparticles by co-precipitation technique. Detailed synthesis procedure had been described in the experimental section. Chemically synthesized ZnO samples were annealed at 300°C and 500°C. These samples have been characterized by doing X-Ray diffraction (XRD), photoluminescence (PL) and Raman spectroscopy. XRD patterns indicate wurzite structure of these samples. SEM pictures shows growth of grain size with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The specific interactions present at each peak are summarized in Table 2. The Raman spectra of TiO 2 and ZnO are like previous studies' results [44,49,53,54].…”
Section: Materials Characterizationsupporting
confidence: 82%
See 1 more Smart Citation
“…The specific interactions present at each peak are summarized in Table 2. The Raman spectra of TiO 2 and ZnO are like previous studies' results [44,49,53,54].…”
Section: Materials Characterizationsupporting
confidence: 82%
“…Based on the peak positions and relative peak intensity, it is confirmed that the tested TiO 2 contains the anatase phase [45][46][47][48]. In the case of ZnO, there are peaks at 102 (s), 333 (w), 439 (s), 586 (w), and 667 (w), which are assigned to the E 2 (LO), E 2 (LO)-E 2 (H), E 2 (H), E 1 (LO), and E 2 (LO)-E 2 (H) modes of Zincite, respectively [49][50][51][52]. The specific interactions present at each peak are summarized in Table 2.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Another vibrational mode at 618 cm −1 , observed for the Zn 0.95 Co 0.05 O composition, is the Co doping effect and is attributed to the F 2g vibrational mode characteristic of ZnCo 2 O 4 . The peak at around 572 cm −1 is due to the A 1 (LO) mode and is linked to the structural disorder in the host lattice, including oxygen vacancy (V O ), zinc interstitial (Zn i ), and their complexes [ 42 , 43 , 44 , 45 ]. An observed change in the intensity of this peak, particularly for the Zn 0.95 Co 0.05 O composition, suggests an increased concentration of oxygen vacancies in this specific composition due to cobalt addition.…”
Section: Resultsmentioning
confidence: 99%
“…The structural characteristics, such as interplanar spacing d(002) and lattice parameters c, were calculated using equations ( 2) and (3). Since the peak was highly dominantly of the (002) plane, the lattice parameters a was determined using the ratio between c and a, (c/a) = 1.633, that specific value of ZnO hexagonal wurtzite structure [32]. The dislocation density (𝛿) represents the number of defect states as dislocation lines in the crystallite grain (nm -2 ).…”
Section: 𝐷 = 𝐾 𝜆 𝛽 ℎ𝑘𝑙 𝑐𝑜𝑠 𝜃 (1)mentioning
confidence: 99%